2016
DOI: 10.15298/arctoa.25.27
|View full text |Cite
|
Sign up to set email alerts
|

Geotropic curvatures of Sphagnum: environmental features of their genesis and trial application for estimation shoot length increment

Abstract: The genesis of geotropic curvatures in the natural habitat of Sphagnum mosses is described in detail on the basis of in situ observations. A novel method of estimation of length increment of Sphagna shoots is developed, based on their geotropic curvatures, which are the markers of physical impacts. The snow load in northern areas is an example of the most typical impact on Sphagnum cover and further geotropic response of stems. Deviation in stem growth causes the curves which may form after snowmelt or under t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 19 publications
(32 reference statements)
1
15
1
1
Order By: Relevance
“…The length increment of S. riparium in this study was 37.9 to 42.2cm, which is among record-high values for this species. A nearly identical increment was previously reported for S. riparium which was found growing 36km away from our range, in the drainage ditches of Rittusuo mire (Mironov et al, 2016). Similar increment levels are also known for other species of wet habitats (Overbeck & Happach, 1957;Brock & Bregman, 1989).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The length increment of S. riparium in this study was 37.9 to 42.2cm, which is among record-high values for this species. A nearly identical increment was previously reported for S. riparium which was found growing 36km away from our range, in the drainage ditches of Rittusuo mire (Mironov et al, 2016). Similar increment levels are also known for other species of wet habitats (Overbeck & Happach, 1957;Brock & Bregman, 1989).…”
Section: Discussionsupporting
confidence: 89%
“…According to Pouliot et al (2010), increment demonstrated by innate markers would be 33-112% higher than when artificial markers are used. According to Mironov et al (2016), this difference for S. riparium is 10-80%.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations